Exotic Food, Food Environment, and Geographical Patterns: Big Data Analytics From Japanese Cuisine in China - Tian, Chuang; Luan, Weixin; Wang, Hui (Frontiers in Earth Science, 2022)
As urban amenity welfare, exotic food is related to consumers’ equal access to diversified food and a healthy diet. This study uses big data provided by an online catering platform to explore Japanese cuisine in China. The field intensity model and spatial econometric model are used to analyze the place effect and its relationship with local socioeconomic factors. The results illustrate that 1) the spatial distribution of Japanese cuisine shows the characteristics of an unbalanced agglomeration distribution, with the coastal economically developed cities as the key layout area and gradually extending to inland cities. 2) Price characteristics indicate that the service target of Japanese cuisine is mainly the middle class. In addition, the spatial inequality of field intensity value indicates that wealthy Eastern cities have more opportunities to enjoy more kinds of and higher quality exotic food. 3) In the local socioeconomic environment, urbanization level, population size, and economic scale are significantly related to inequal access to Japanese cuisine. The essential mechanism of these circumstances is the internal needs of pricing characteristics and the negative externalities caused by unequal urban infrastructure.